Manajemen Strategis Madrasah Berbasis Komputer dan Pesantren di Madrasah Aliyah Zainul Hasan 1 Genggong - Seftianingrum, Silviana; Izzah, Ismatul; Yunita, Arifia Retna (Attractive : Innovative Education Journal, 2024)
In the era of globalization and the development of science and technology (IPTEK), Islamic boarding schools are also required to further improve their quality, both in the religious, intellectual and life skills fields, so that the existence of Islamic boarding schools remains strong. Apart from that, with the assumption that not all Islamic boarding school graduates will become ulama or kiai, and choose employment in the field of religion, then other skills such as educational skills and skills which are part of life skills need to be given to the students before the students enter the field. in the midst of real society. The aim of this research is to determine the management strategy for computer-based madrasas and Islamic boarding schools at Madrasah Aliyah Zainul Hasan 1 Genggong. This type of research is qualitative research. Meanwhile, the researcher's data collection methods used observation, interviews and documentation methods. Based on the data obtained after conducting research and analyzing all the data obtained by researchers, it can be found that Madrasah Aliyah Zainul Hasan 1 Genggong also keeps up with current developments, especially in the field of technology, but the Madrasah does not eliminate Islamic boarding school customs. Keywords: Madrasah management strategy, qualitative research methods